STRUKTUR KEPEMILIKAN MANAJERIAL, STRUKTUR KEPEMILIKAN INSTITUSIONAL, DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN DAN DAMPAKNYA TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SEKTOR PERTAMBANGAN BATUBARA PADA TAHUN 2017-2019 - Rina Malahayati (Department of Accounting, Faculty of Economics & Business, 2021)
This study is aimed to examine the influence of managerial ownership structure, institutional ownership structure, and firm size on company performance and the impact on the earning management on companies of sector coal mining in 2017 – 2019. Unit analysis are companies listed on coal mining for period 2017-2019. The population are 75 observations (25 companies x 3 years). Data processing uses panel data processed by using SPSS. For testing the hypothesis, the study uses path analysis. The result showed that (1) managerial ownership structure, institutional ownership structure, and firm size simultaneously to company performance, (2) the managerial ownership structure no effect on company performance, (3) the institutional ownership structure effect to negatively on company performance, (4) the firm size effect to positively on company performance, and (5) the company performance effect to negatively on earning management.